Bovine helper T-cell clones specific for lymphocytes infected with Theileria parva (Muguga) - Baldwin, Cynthia L.; Goddeeris, M.; Morrison, W. Ivan (Wiley, 1987)
SummaryT‐cell clones specific for lymphocytes infected withTheileria parvawere derived from animals immunized by infection withT. parva(Muguga). These clones were non‐cytolytic and had the BoT4+BoT8‐surface phenotype, BoT4 and BoT8 being the bovine analogues of human CD4 and CD8 molecules. The clones proliferated in response to irradiated autologous lymphoblasts infected withT. parva(Muguga) but not to autologous uninfected lymphoblasts or monocytes. They were parasite strain‐specific, in that they did not respond to autologous lymphoblasts infected with another parasite stock,T. parva(Marikebuni). The clones proliferated in the absence of exogenous T‐cell growth factor (TCGF) and produced TCGF when stimulated with concanavalin A. Induction of proliferation of the cloned T‐cells was genetically restricted, and evidence was obtained which indicated that they were restricted by determinants on class II major histocompatibility complex (MHC) molecules. These findings demonstrate that infections withT. parvastimulate antigen‐specific MHC‐restricted T‐cells with the properties of T‐helper cells. The results also provide further evidence for the expression of a parasite strain‐specific antigen on the surface ofT. parva‐infected lymphocytes.